AKAD-AKAD DALAM ASURANSI SYARIAH - Noer Hasanah; Anna Zakiyah Hastriana (Sahaja: Journal Sharia and Humanities, 2024)
Every transaction contained in Islamic insurance must use the contracts that have been determined. In Islamic insurance, contracts are written agreements that cover all relevant risks and thel obligations andl rights ofl the partiesl in accordancel with Islamic principles. The contract is an important component of the practice of Islamic insurance. Which in the contract is classified into several types, including Tabarrul 'Akad, Tijarahl Akad, Mudharabah Akad, Wakalahl bil Ujrahl Akad, and Mudharabahl Musytarakah lAkad. These contracts are agreements between insurance companies and their client companies that must adhere to sharia principles regarding the prohibition of usury, maysir, and gharar. Tabarru' Akad aims to involve one participant with other participants by providing tabarru' funds which are expected to help each other among insurance participants. While Akad Tijarah is intended for profitability purposes using the mudharabah principle. Therefore, itl is veryl important forl Muslims tol know thel contracts andl mechanisms used by Islamic insurance when conducting transactions for insurance participants. This writing aims to explain the various contracts in Islamic insurance along with the definition ofl these contractsl and theirl application to Islamicl insurance products. This research methodl uses a literature study which takes from several literatures through journals and books.